CWDM demultiplexer using anti-reflection, contra-directional couplers based on silicon nitride rib waveguide. (December 2019) - Zubkova, E; Golikov, A; An, P; Kovalyuk, V; Korneev, A; Ferrari, S; Pernice, W; Goltsman, G
Abstract: We report on the development and fabrication of a 9-channel coarse wavelength-division multiplexing for telecommunication wavelengths (1550 nm) using anti-reflection contra-directional couplers, based on silicon nitride (Si3 N4 ) rib waveguide. The transmitted and reflected spectrum in each channel of the demultiplexer were measured. The average full width at half maximum of the transmitted (reflected) spectra is about 3 nm.